NILAI-NILAI ETIKA ARISTOTELES DALAM MEWUJUDKAN PERDAMAIAN MANUSIA INDONESIA - Adus Pinus Dandi (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2023)
This article aims to "understand Aristotle's ethical values ​​in realizing Indonesian human peace". Ethics is the science that deals with human behavior. Behavior itself is divided into two, namely good behavior and bad behavior. Something is said to be good or bad is called moral consciousness. Moral awareness as a basis for consideration for the actions of human life to achieve the goal of reconciling happiness. For Aristotle ethics is the goal of life to achieve happiness, so good behavior and having moral values ​​are actions that are directed towards achieving happiness that reconcile humans in living their daily lives. According to Aristotle, good deeds are actions that are done rationally and are accompanied by virtue. Humans basically want happiness that reconciles himself and his environment. Moving on from all that, the author provides an understanding of Aristotle's ethical values ​​for Indonesian people to obtain happiness that reconciles themselves and their environment by obeying the norms that apply in society so that the real human desire is achieved, namely peace.